Autonomy in Philanthropy: A Model for Nonprofit Organizations. (30th November 2022) - Harkema, Beverly
Abstract: People seem to think of autonomy merely as freedom or liberty, and of philanthropy only as charity or voluntary goodwill. These conceptualizations are simplistic and fail to address the ethical and societal implications of who gets to choose, the effects of their choices, who receives philanthropy and why they need it. In the United States, nonprofit organizations especially wrestle with these questions, as they are the primary vehicles for philanthropic action, but where autonomy is increasingly restricted, for both stakeholders and organizations themselves. This paper examines autonomy historically and theoretically, to robustly define autonomy to include aspects of consequences, duty, character, responsibility, and capacity, all of which inherently influence and are influenced by philanthropy. A model is presented that can pragmatically visualize the complexity of autonomy in order to argue for its maximization, as it considers autonomy's dimensions and the environment of norms/expectations and trends/changes within which nonprofit organizations can express or fail to express autonomy.